Социология и идеология в ракурсе постмодерного мышления - Танчер, В. (Социология: теория, методы, маркетинг, 2000)
Interrelation of sociology with ideology have subjected to argument since the formation of this branch of science. In the present-day situation the traditional problem of the ideologization of sociological knowledge is perceived from the post-modern viewpoint as a rejection of modernist ideological garment — both bourgeois and communist. Instead, the slogan of “ideology of professionalism” is propounded. In the article the points of view of A.Giddens, R.Collins, Z.Bauman, J.Alexander et al. are analyzed in the context of the problem discussed.